The Influence of School Culture and Motivation on Student Achievement - Eti Suheti; Maria Emilia Tyas Wulan Wahyu Dhati (International Journal of Education, Information Technology, and Others, 2021)
In this era of advanced technology, the role of educators must be able to keep up with the times in providing knowledge to students by following the currently developing culture. School culture within certain limits and motivation can encourage student achievement. This research can be seen from the coefficient of determination (R2) with a regression coefficient of 0.219 showing the effect of the School Culture and Motivation variables together on the Student Achievement variable is 29.1% while the rest 70.9% determined by other factors not examined. Simultaneous closeness of the relationship between the variables of School Culture, Motivation, and Student Achievement is quite strong (0.540).